2021
DOI: 10.2174/1874944502114010545
|View full text |Cite
|
Sign up to set email alerts
|

Association between Awareness on Antibiotic Resistance and Antibiotic Misuse Among Saudi University Students

Abstract: Background: Saudi Arabia has the highest prevalence of resistant pathogens in the Gulf Region, with a rapid increase in antibiotic resistance seen in recent years. Misuse is common despite laws prohibiting dispensing antibiotics without prescription. This study was conducted to determine the association between awareness of antibiotic resistance and antibiotic misuse among Saudi university students. Specifically, it aimed to determine the proportion of university students who were aware of anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
0
0
Order By: Relevance
“…Antimicrobial resistance (AMR) is a life-threatening public health burden worldwide due to resistant microorganisms due to antibiotic abuse and overuse [ 11 , 14 , 17 ]. It was included in the 10 top global public health threats facing humanity by the WHO [ 1 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Antimicrobial resistance (AMR) is a life-threatening public health burden worldwide due to resistant microorganisms due to antibiotic abuse and overuse [ 11 , 14 , 17 ]. It was included in the 10 top global public health threats facing humanity by the WHO [ 1 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted in Saudi Arabia have found that there is a lack of awareness about AMR and the proper usage of antibiotics among the general population, with only 40.5% having sufficient knowledge about AMR, while 75% of medical and health-related science students and 71.5% of community pharmacists followed good practices in dispensing antibiotics [15][16][17]. Research has indicated that education is an effective and cost-saving strategy to improve the correct antibiotic use and reduce AMR [18].…”
Section: Introductionmentioning
confidence: 99%